Asian cuisine - Banzuelo, Loida R. (Manila, Philippines : Mindshapers Co. Inc., 2020)
Asian Cuisine is the culmination of the Chinese, European, Islamic, Hinduism and Christian influences as proven by the balance of flavors, refinement and a distinct creativity of food presentation.
CHAPTER 1. Overview of Asian cuisine -- 2. Philippine Cuisine -- 3. Japanese cuisine -- 4. Chinese Cuisine -- 5. Korean Cuisine -- 6. Vietnamese cuisine -- 7. Thai Cuisine -- 8. Indonesian Cuisine -- 9. Indian Cuisine.
Includes bibliographical references.
Keywords: COOKING, ASIAN